ANALYZE THE IMPLEMENTATION OF ORGANIZATIONAL CULTURE TO THE EMPLOYEE PERFORMANCE AT PT. DIMEMBE NYIUR AGRIPRO - Hulima, Risky Ramadhansyah (Sam Ratulangi University, 2016)
Employee performance is one of the important aspects in human resource management systems in company. This research focused on the implementation of organizational culture to the employee performance in the coconut flour company. This research used qualitative research method. The respondents of this research were the Director and managers who have implemented organizational culture and it also included employees from different divisions of job field and who have worked for at least more than 6 months in the company. The research adopted in depth interviews to gather data from employees in order to measure their opinions about the implementation of organizational culture in the company and their working performance. This research found that the implementation of organizational culture in the company is greatly affected and positively influences on the performance of employee.